2020
DOI: 10.1002/mats.202000032
|View full text |Cite
|
Sign up to set email alerts
|

Star Polymer Translocation into a Spheroidal Cavity

Abstract: Star polymer translocation into a spheroidal cavity has been studied using Langevin dynamics simulations. To isolate the effect of polymer architecture, the total number of monomers, N, is kept constant while the number of arms, f, is varied. For the special case of a spherical cavity, the mean translocation time, τ, exhibits nonmonotonic variation with f for large cavities, but decreases monotonically with f for sufficiently small cavities. The value of τ for a prolate cavity is generally similar to that for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…[60] Moreover, the authors also employed LD simulations to investigate star polymer translocation into a spheroidal cavity subject to an external electric field inside the pore. [61] For a fixed value of the chain total mass, they found that 〈τ〉 displays non-monotonic variation with respect to f for large cavities, while it decreases monotonically with f for sufficiently small cavities.…”
Section: Introductionmentioning
confidence: 96%
“…[60] Moreover, the authors also employed LD simulations to investigate star polymer translocation into a spheroidal cavity subject to an external electric field inside the pore. [61] For a fixed value of the chain total mass, they found that 〈τ〉 displays non-monotonic variation with respect to f for large cavities, while it decreases monotonically with f for sufficiently small cavities.…”
Section: Introductionmentioning
confidence: 96%
“…[51] Zhang and Luo have studied the driven translocation of a polymer into a circular confinement through a small pore, and found that the scaling exponent of the translocation time with the polymer length is dependent on the driving force and the monomer density of the whole polymer in the circular confinement. [52] Other studies indicated that the packaging of polymers into a cavity is a complex dynamical process, which is affected by many other factors, such as the attractive interaction between the polymer and the inner wall of the cavity, [30] the geometry of the cavity, [53][54][55] the flexibility of the polymer, [51,56] the temperature of the solvent, [57] the topology of the polymer, [58] etc.…”
Section: Introductionmentioning
confidence: 99%